MAKNA RAGAM HIAS PADA FASAD BANGUNAN (STUDI KASUS : KELENTENG BAN HING KIONG, MANADO) - Wulanningrum, Sintia Dewi (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2018)
Ban Hing Kiong Temple was founded in 1819 and is the oldest temple in North Sulawesi. The advantages of Ban Hing Kiong Temple are; strategically located at the center of the city that is reachable by public transportation and is the center of China Town where temples, houses, shrines and markets belonging to the Chinese ethnic can be found, as well as two cannons belonging to VOC, therefore, it is a religious center as much as it is a historical tourist destination. In addition, this temple possesses a unique design with Classical Chinese architectural style decorated with a variety of motifs. Motifs found in this Temple is one of many attractions for visitors. Motif is a basic form of decoration that will usually become a repeated pattern in a craft or art work (Purnomo, 2013). Every motif in Ban Hing Kiong Temple has different type and meaning. This research aims to identify the types and meanings of motifs on the exterior of Ban Hing Kiong Temple. The method used is descriptive qualitative by identifying the types of motifs and the meanings of motifs through literature studies and field survey. This study found that there are three types of motifs on the building exterior, including; flora motif, fauna motif, geometric and motif about legends. The most common motif found on the exterior is fauna motif in the form of dragon and tiger ornaments found in the building column, on building roofs, walls, and incense burners. Kelenteng Ban Hing Kiong berdiri sejak tahun 1819 dan merupakan Kelenteng tertua di Sulawesi Utara.. Kelebihan Kelenteng Ban Hing Kiong  antara lain; letaknya strategis berada di tengah kota yang dapat ditempuh dengan transportasi umum dan  merupakan  pusat China Town yang terdapat terdapat kuil, rumah-rumah, tempat suci dan pasar milik etnis Cina, terdapat dua buah meriam peninggalan VOC, sehingga selain sebagai pusat religi juga sebagai tujuan wisata sejarah. Selain itu, Klenteng ini memiliki desain yang unik dengan gaya arsitektur Cina Klasik yang  dihiasi dengan ragam ragam hias. Ragam hias yang ada di Kelenteng merupakan salah satu daya tarik bagi pengunjung. Ragam hias adalah bentuk dasar hiasan yang biasanya akan menjadi pola yang diulang-ulang dalam suatu karya kerajinan atau seni (Purnomo, 2013). Setiap ragam hias di Kelenteng Ban Hing Kiong memiliki tipe dan makna yang berbeda-beda. Penelitian bertujuan untuk mengidentifikasi jenis dan makna ragam hias pada fasad Kelenteng Ban Hing Kiong. Metode Penelitian adalah deskriptif kualitatif dengan mengidentifikasi jenis ragam hias serta makna ragam hias melalui studi pustaka dan survey lapangan. Hasil penelitian yaitu terdapat tiga jenis ragam hias pada fasad bangunan antara lain; ragam hias flora, ragam hias fauna, geometris dan ragam hias legenda. Ragam hias yang paling banyak ditemukan pada fasad yaitu ragam hias fauna berupa ornamen naga dan macan yang berada pada kolom bangunan, atap bangunan, dinding  serta tempat pembakaran hio.